Work motivation and occupational self-efficacy belief to continue working among ageing home care nurses: a mixed methods study - Stina Wallin; Anncristine Fjellman-Wiklund; Lisbeth Fagerström (BMC, 2022)
Abstract Background It is important to support ageing home care nurses (HCNs) to remain in work for longer, since the need for home care services is increasing. Personal resources such as self-efficacy belief contribute to work ability, as does work motivation. Few studies have targeted the ageing workers' self-efficacy belief to manage their final working years. This study explores ageing HCNs' work motivation, and occupational self-efficacy, i.e. belief in one's capabilities, to continue working until expected retirement age. Methods The design of the study is exploratory using a mixed method with a qualitative to quantitative approach. A total of 234 HCNs answered four open-ended questions from a cross-sectional survey, regarding their work motivation and self-efficacy beliefs. First, data was analysed using manifest qualitative content analysis. Next, a quantitative analysis was performed based on the results of the qualitative study, and the categories that emerged were quantitatively ranked. Results The open-ended questions yielded 2339 utterances. The findings showed that several categories concurrently affected both work motivation and self-efficacy belief. When they were well-functioning, they positively affected both work motivation and self-efficacy belief, and when they were insufficient, they negatively affected either or both motivation and/or belief. Meaningfulness, job satisfaction, social support, and work environmental and organizational characteristics affected work motivation most. Perceived health highly affected the self-efficacy belief to continue working until expected retirement age, as well as meaningfulness of work, support from colleagues and home care managers, and work characteristics. Conclusions Through highlighting the meaningfulness of work, and supporting the perceived health, the work community and leadership, both work motivation and self-efficacy belief to continue working might be facilitated among ageing HCNs. However, the still present draining workload must be handled.